A comparison of temperature and freeze-thaw effects on high-swelling and low-swelling soils stabilized with xanthan gum - Sahand Fateh; Yasaman Mansourkiaei; Mohammad Mahdi Shalchian; Mahyar Arabani; Meghdad Payan; Payam Zanganeh Ranjbar (Results in Engineering)
Clay soils necessitate enhancement owing to their inadequate strength characteristics in geoengineering. The utilization of biopolymers is a new bio-stabilization technique for clayey soils with no environmental disadvantages associated with traditional additives. The present research aims to evaluate the performance of varying concentrations of xanthan gum biopolymer (0.5, 1, and 2 %) concerning the strength and durability characteristics of two types of soil: kaolinite and bentonite, over varied curing time. For this purpose, tests were performed on compaction, compressive strength, free swelling, freezing and thawing, temperature effects, and microstructure to analyze the interaction between soil particles and biopolymer in both soils. The results indicated that the 1 % xanthan gum sample with a 28-day curing period had superior performance in both soil types, with a compressive strength enhancement of 457 % for kaolinite and 274 % for bentonite. The swelling test indicated that the optimal incorporation of biopolymer into kaolinite soil augmented swelling by 6 %, whereas the swelling of bentonite diminished up to 88 %. The freeze-thaw test demonstrated that as the number of cycles increased, the strength of the soil diminished; nevertheless, bentonite had a lesser decline in strength relative to kaolinite. Analysis of varying temperatures (40–70–100) revealed that optimal resistance performance in both soils occurs at 70 °C; however, the temperature's influence on the strength of stabilized bentonite is more pronounced. According to the findings, the addition of xanthan gum improves soil strength, hence increasing the feasibility of this stabilizer in practical applications such as landfills, embankments, and slopes.